Strategi Pemberdayaan Perempuan Melalui UMKM Berbasis Ketersediaan Potensi Lokal di Desa Negeri Lama - Hendri Dony Hahury; Muspida Muspida; Jeane B. Nikijuluw; Jopie Tamtelahitu; Dientje Rumerung; Hermi Oppier (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2025)
Women are often viewed solely as domestic workers responsible for taking care of household needs and requirements. Yet, women have the opportunity to find employment and earn income, thus ensuring the sustainability of household livelihoods. In a microeconomic context, income inequality exists between women and men in various countries, both developing and developed. This income inequality can be addressed by optimizing the local potential of each region through MSMEs. This reality is further complicated when faced with the geographical location of archipelagic regions that possess unique natural resource potential for development, yet many residents live below the poverty line. The solution to empowering women through MSMEs based on local potential involves fostering awareness of women's potential, strategies for overcoming inhibiting stereotypes, strategies for overcoming psychological barriers, and empowering women to run their businesses.